Heart Rate Recovery and Oxygen Kinetics After Exercise in Obstructive Sleep Apnea Syndrome - Nanas, Serafim (Clin Cardiol, 2010)
BACKGROUND: Patients who suffer from obstructive sleep apnea (OSA) have a decreased exercise capacity and abnormal autonomic nervous function. However, the kinetics of early oxygen (O(2)) and heart rate recovery (HRR) have not been described. MATERIALS AND METHODS: We evaluated 21 men with moderate to severe OSA (mean age: 48 ± 11 yrs, mean apnea‐hypopnea index [AHI]: 55 ± 13) and without known heart disease and 10 healthy men matched for age and body mass index (BMI; controls). Men with OSA underwent overnight polysomnography, and both groups underwent symptom‐limited incremental cardiopulmonary exercise testing (CPET). We recorded the CPET parameters including peak O(2) uptake (Vo (2)p), kinetics of early O(2) recovery by the first degree slope of Vo (2) during the first minute (Vo (2)/t slope), the time required for a 50% decline of Vo (2)p during recovery (T(1/2)), and early heart rate recovery (HRR = HR at maximal exercise − HR at 1 min of recovery), as well as the chronotropic reserve to exercise ([CR] = [peak HR − resting HR/220 − age − resting HR] × 100). Patients with OSA had a lower Vo (2)p (28.7 ± 4.0 vs 34.7 ± 6.2 mL/kg/min), Vo (2)/t slope (1.04 ± 0.3 vs 1.4 ± 0.17 mL/kg/min(2)), and T(1/2) (74 ± 10 vs 56 ± 6 sec) compared to controls (all P < 0.001). In addition, both HRR and CR were lower in the OSA group (22.0 ± 7.0 vs 31.0 ± 6.0 bpm, P:0.003, and 79.0% ± 15% vs 99.0% ± 13.0%, P:0.01, respectively). CONCLUSIONS: Patients with OSA demonstrate reduced exercise capacity, delayed oxygen kinetics, and reduced HRR. These data point to abnormal oxygen delivery and/or oxidative function of the peripheral muscles and impaired autonomic nervous activity in OSA patients. Copyright © 2010 Wiley Periodicals, Inc.